An Efficient Density-Based Clustering Algorithm for the Capacitated Vehicle Routing Problem - Zhang, Jiashan (International journal of advanced network, monitoring, and controls, 2017)
The capacitated vehicle routing problem (CVRP) is one of the most challenging problems in the optimization of distribution. Most approaches can solve case studies involving less than 100 nodes to optimality, but time-consuming. To overcome the limitation, this paper presents a novel two-phase heuristic approach for the capacitated vehicle routing problem. Phase I aims to identifying sets of cost-effective feasible clusters through an improved density-based clustering algorithm. Phase II assigns clusters to vehicles and sequences them on each tour. Max-min ant system is used to order nodes within clusters . The simulation results indicate efficiency of the proposed algorithm.